PERAN FEMVERTISING DALAM MEMBENTUK PERILAKU KONSUMEN: TINJAUAN LITERATUR SISTEMATIS - Kristin Wulansari; Siti Shoimah; Eka Agustiningtias; I Gede Iwan Suryadi; Thomas Evi Viktor Rahajaan (J-MACC, 2026)
This study examines the influence of femvertising on consumer behavior through a systematic literature review. Femvertising refers to advertising that promotes women’s empowerment, independence, and gender equality, and has become increasingly relevant in modern marketing. Using the PRISMA framework, this review analyzed 26 English-language journal articles published between 2013 and 2024 and sourced from the open access Emerald database. The review focused on research themes, methods, geographic contexts, and theoretical perspectives related to femvertising and consumer behavior. The findings show that femvertising generally generates positive consumer responses, especially among women, by improving attitudes toward advertisements, strengthening brand evaluations, and increasing purchase intention. However, its effectiveness is influenced by several factors, including gender differences, emotional engagement, support for women’s rights, feminist self-identification, perceived authenticity, and socio-cultural context. The review also indicates that male and female consumers may respond differently to empowerment-based and gender-stereotypical advertising. In addition, consumers are becoming more critical in assessing whether empowerment messages reflect genuine brand commitment or merely symbolic marketing. These findings suggest important implications for marketers seeking inclusive, effective, and culturally sensitive advertising strategies.